Decolonizing Indigenous health: Generating a productive dialogue to eliminate Rheumatic Heart Disease in Australia. (May 2021) - Haynes, Emma; Walker, Roz; Mitchell, Alice G.; Katzenellenbogen, Judy; D'Antoine, Heather; Bessarab, Dawn
Abstract (300 words): In common with colonized Indigenous people worldwide, many Australian Aboriginal people experience inequitable health outcomes. While the commitment and advocacy of researchers and health practitioners has resulted in many notable improvements in policy and practice, systemic and structural impediments continue to restrain widespread gains in addressing Indigenous health injustices. We take Rheumatic Heart Disease (RHD), a potent marker of extreme health inequity, as a case study, and critically examine RHD practitioners' perspectives regarding the factors that need to be addressed to improve RHD prevention and care. This study is an important explanatory component of a broader study to inform new clinical practices, and health system strategies and policies to reduce RHD. A decolonising, critical medical anthropology (CMA) analysis of findings from 22 RHD practitioner in-depth interviews conducted in May 2016 revealed both practitioners' perceptions of health system shortcomings and a sense of hopelessness and powerlessness to transform existing health system inequities, the negative impacts of which were subsequently confirmed in a separate study of RHD patients' lived realities. We reveal how biomedical dominance, normalized deficit discourses and systemic racism influence the current policy and practice landscape, narrowing the intercultural space for productive dialogue and reinforcing the conditions that cause disease. To counter biomedical approaches that contribute to existing health inequities in health care, we recommend localized, strength-based, community-led research projects focused on actions that use critical decolonizing social science approaches to achieve system change. We demonstrate the importance of integrating biological and social sciences approaches in research, education/training, and practice to: 1) be guided by Indigenous strengths, knowledges and worldview, and 2) adopt a critical reflexive stance to examine systems, structures and practices. Such an approach facilitates productive cross-cultural dialogue and social transformation; providing direction and hope to practitioners, enhancing their knowledge, skills and capacity and improving Aboriginal health outcomes. Highlights: Biomedical approaches result in normalization of deficit discourses and racism. Biomedicine limits practitioners' critical and reflective skills and sense of agency to address inequities. Cultural safety, including reflexivity regarding power and privilege is needed. Changes in systems and practice requires a combination of Indigenous knowledges, biomedical and social science approaches